2019
DOI: 10.2460/ajvr.80.8.727
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of allometric scaling as a tool for extrapolation of the enrofloxacin dose in American black vultures (Coragyps atratus)

Abstract: OBJECTIVE To determine the pharmacokinetics of enrofloxacin after IV administration in American black vultures (Coragyps atratus), to compare clearance of enrofloxacin in American black vultures with clearance of this fluoroquinolone in other avian species, and to evaluate whether allometric scaling is an appropriate tool for dose extrapolation in avian species. ANIMALS 6 healthy adult American black vultures. PROCEDURES Enrofloxacin concentrations were quantified by use of high-performance liquid chromato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Mean absorption time (MAT) was calculated as MRT IM , SC , oral – MRT IV . The body extraction ratio ( E body ) for tolfenamic acid after IV administration is calculated using Cl T /QC (Toutain & Bousquet‐Melou, 2004), and QC (ml kg −1 min −1 ) is the cardiac output calculated according to the allometric equation with 290.7 × body weight (in kg) 0.69 (Grubb, 1983; Waxman et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Mean absorption time (MAT) was calculated as MRT IM , SC , oral – MRT IV . The body extraction ratio ( E body ) for tolfenamic acid after IV administration is calculated using Cl T /QC (Toutain & Bousquet‐Melou, 2004), and QC (ml kg −1 min −1 ) is the cardiac output calculated according to the allometric equation with 290.7 × body weight (in kg) 0.69 (Grubb, 1983; Waxman et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…After intramuscular administration, enrofloxacin showed a rapid and complete absorption, reaching high Cmax and AUC values. Taking into account AUC values from previously published data on intravenously administered enrofloxacin to black vultures [ 8 ], a bioavailability value of 90% is estimated. This finding is in agreement with values described in other avian species, which oscillated between 90% and 99% [ 13 , 18 , 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…If AUC is corrected by the administered dose (AUC/D), in general, birds of prey show high values, black vultures showing the highest one (vultures 7.39; great horned owls 4.35, red tailed hawks 3.60; caracaras 3.44 kg h/L), while ratites show very low values [ 22 , 23 , 24 ]. These findings could be related to a slow enrofloxacin clearance and a low extraction ratio observed in vultures after intravenous administration [ 8 ]. This behaviour could also be related to a long enrofloxacin permanence in black vultures, since elimination half-life showed values higher than 18 h. Compared to other avian species, we observed that vultures present the longest body permanence, with an elimination half-life almost double that observed in chickens (10.6 h) [ 19 ], and is almost 20 times longer than in ostriches [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma concentrations of danofloxacin from each goose were analyzed with a non-compartmental analysis using WinNonlin The body extraction ratio (E body ) for danofloxacin after IV administration was calculated using Cl T /QC (Toutain & Bousquet-Melou, 2004), and QC (mL/kg/min) was the cardiac output calculated according to the allometric equation with 290.7 × body weight (in kg) 0.69 (Grubb, 1983;Waxman et al, 2019).…”
Section: Pharmacokinetic Analysismentioning
confidence: 99%